Potential of canopy tourism in Malaysia - Ramlan, Mohd Aswad; Aziz, Azlizam; Yahya, Noor Azlin; Abdul Kadir, Nik Azyyati; Yacob, Mohd Rusli (Forestry Department Peninsular Malaysia, 2012)
The canopy walkway, a structure for observing the upper part of forest canopy was first built in Malaysia in the early 1960s. Initially, the structure was built purely for research, but later opened to the public as an attraction in natural areas. This paper discusses the potential of canopy tourism in Malaysia, its evolution, as a tool in conservation and strategies for the sustainability of canopy tourism while serving as a recreational facility in our forests.